2001
DOI: 10.1590/s0004-282x2001000200025
|View full text |Cite
|
Sign up to set email alerts
|

Neuropatia vasculítica na granulomatose de Wegener: relato de caso

Abstract: RESUMO -O acometimento neurológico no curso da granulomatose de Wegener atinge 15-50% dos pacientes, porém como sintomatologia inicial não é comentado na literatura. Relatamos o caso de uma paciente com mononeurite múltipla secundária a granulomatose de Wegener, enfocando os aspectos de antecipação do quadro neurológico em relação aos sintomas sistêmicos, a contribuição diagnóstica da biópsia do nervo sural e a boa evolução do quadro neurológico. PALAVRAS-CHAVE: granulomatose de Wegener, neuropatia, vasculite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Peshin et al [ 12 ] and Lew et al [ 13 ] also reported two such cases, but they had evidence of vasculitis on examination in the form of nailbed changes and Raynaud's phenomenon, respectively. Apart from these, there is one case report in German literature and one in a Portuguese journal on mononeuritis multiplex as the initial manifestation of GPA [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peshin et al [ 12 ] and Lew et al [ 13 ] also reported two such cases, but they had evidence of vasculitis on examination in the form of nailbed changes and Raynaud's phenomenon, respectively. Apart from these, there is one case report in German literature and one in a Portuguese journal on mononeuritis multiplex as the initial manifestation of GPA [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%